2020
DOI: 10.3390/endocrines1010006
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Stem Cell Research of the Pituitary Gland and Pituitary Adenoma

Abstract: Regenerative medicine and anti-tumoral therapy have been developed through understanding tissue stem cells and cancer stem cells (CSCs). The concept of tissue stem cells has been applied to the pituitary gland (PG). Recently, PG stem cells (PGSCs) were successfully differentiated from human embryonic stem cells and induced pluripotent stem cells, showing an in vivo therapeutic effect in a hypopituitary model. Pituitary adenomas (PAs) are common intracranial neoplasms that are generally benign, but treatment re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…PIT1 (also known as POU1F1), a POU domain-containing transcription factor, is essential for the terminal cell differentiation and gene expression of normal pituitary cells that go on to secrete the neuroendocrine hormones PRL, GH, and TSH [11]. The formation of these normal pituitary cells of the PIT1 lineage is positively regulated by PROP1 and negatively regulated by HESX1 [20].…”
Section: Development Of Normal Pituitary Cells Of the Pit1-lineagementioning
confidence: 99%
“…PIT1 (also known as POU1F1), a POU domain-containing transcription factor, is essential for the terminal cell differentiation and gene expression of normal pituitary cells that go on to secrete the neuroendocrine hormones PRL, GH, and TSH [11]. The formation of these normal pituitary cells of the PIT1 lineage is positively regulated by PROP1 and negatively regulated by HESX1 [20].…”
Section: Development Of Normal Pituitary Cells Of the Pit1-lineagementioning
confidence: 99%
“…In general, tumor stem cells are derived from normal tissue specific cells or re-differentiate and/or de-differentiate from progenitor/differentiated cells. Some studies have discussed the relationship between genetic alterations in human pituitary gland stem cells and tumors formed from pituitary adenoma stem cells (PASCs) [ 76 , 77 ]. While stem-like cells are particularly resistant to classical cytotoxic drugs due to the overexpression of drug-extruding pumps and DNA-repairing enzymes [ 77 ], many previous studies demonstrated a higher sensitivity of tumor stem cell subpopulation to metformin [ 78 ], which may lead to the development of a DR approach in PitNETs [ 79 , 80 ].…”
Section: Pituitary Neuroendocrine Tumormentioning
confidence: 99%